Esophageal stenosis after chemotherapy for breast cancer: A case report. Issue 11 (18th March 2022) - Ou, Zhen-Fei; Ren, Lin-Lin; Yin, Xiao-Yan; Zhang, Cui-Ping; Xu, Yong-Hong; Min, Cong-Cong
Abstract: Rationale: Esophageal stenosis after chemotherapy in breast cancer patients is rare. Distinguishing esophageal stenosis from esophageal metastasis caused by breast cancer is important. Patient concerns and diagnosis: A 62-year-old woman diagnosed with advanced breast cancer and no distant metastases gradually developed skin changes, oral ulcers and mucosal injures after four cycles of chemotherapy. Dysphagia was the most severe symptom that greatly affected the patient's quality of life. Ultimately, esophageal stenosis and ulceration were confirmed by serial radiological examinations and endoscopic biopsy. Interventions: Due to difficulties in eating orally, the patient was initially placed on a nasogastric tube in order to improve her nutritional status. Simultaneously, she was administered powerful proton pump inhibitors. She underwent modified radical mastectomy for breast cancer after her nutritional status improved. However, the patient was still suffering from severe dysphagia after more than 4 months of follow-up. Subsequently, she underwent removable esophageal stent implantation after after unsuccessful attempts to dilate her esophagus. Outcomes: The dysphagia symptoms were immediately alleviated to a certain degree, and the dilated cavity of the upper esophagus showed slight retraction. Lessons: Esophageal stenosis is very infrequent in patients with breast cancer after chemotherapy. It needs to be. distinguished from esophageal metastasis caused by breast cancer. Esophageal stent implantation may provide benefits in terms of both symptom control and survival in patients with severe esophageal structures.